Analytical chemistry scenarios - Crowther, David (The University of Hull)
Pre-lab exercises, pre-lab tests, lab scripts and post-lab questions for two scenarios in analytical chemistry ("Is it the Real Thing?" and "Chemistry at the Night Club"). Written for second year undergraduste module for chemistry and bioscience students. Could be used from first year undergraduate to Masters level with modifications. Stored here as a self-extracting .rar file - save it to your computer, then double click on it to extract files. Documents are in .rtf format for easy modification.